(untitled) (Fiep Bulletin - online, 2017)
This article is a bibliographical review, where the electronic databases and electronic journals were consulted,such as Bireme and Scielo and the Ministry of Health, in order to verify the benefits that exercise practice Physical activity can bring toindividuals living with HIV / AIDS and making use of antiretroviral therapy as well as provide information essential for the prescriptionof physical activity appropriate for this population. From the studies carried out, it was possible to verify that the resistance trainingbrings numerous benefits to people living with HIV / AIDS, however it was possible to observe that when combined with aerobictraining the results are more satisfactory.